EFEKTIVITAS PELATIHAN “TANGGA KEBERHASILAN” TERHADAP EFIKASI DIRI, KECEMASAN BEBICARA DI DEPAN UMUM DAN ACHIEVEMENT GOAL ORIENTATION ACADEMIC PADA MAHASISWA - Dani Yoselisa; M. Antos Riady; Syifa Farah Madani; Silvia M (Universitas Negeri Padang, 2024)
The results of this study found that the training was effective and influential in increasing self-efficacy, with a Wilcoxon Z value = -2.673 (p <0.05) and a Mann Whitney value = 52.5 (p <0.05). The average self-efficacy in the experimental group (M = 19.5) was higher than in the control group (M = 11.5). This training is also effective in increasing achievement goal orientation academic with Wilcoxon Z value = -3.126 ( p < 0.01) and Mann Whitney value = 23.5 (p < 0.01). ). The average Achievement goal orientation academic in the experimental group (M = 21.43) is higher than the control group (M = 9.57). However, there is no effect of training on public speaking anxiety in students, with Wilcoxon Z value = -1.915 ( p = 0.056 > 0.05) and Mann Whitney value = 76.5 ( p = 0.135 > 0.05). So, the training has a significant effect on increasing self-efficacy and achievement goal orientation academic students, but is not effective in reducing public speaking anxiety.